If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -3(2x + -1) = 2 Reorder the terms: 2 + -3(-1 + 2x) = 2 2 + (-1 * -3 + 2x * -3) = 2 2 + (3 + -6x) = 2 Combine like terms: 2 + 3 = 5 5 + -6x = 2 Solving 5 + -6x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -6x = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -6x = 2 + -5 -6x = 2 + -5 Combine like terms: 2 + -5 = -3 -6x = -3 Divide each side by '-6'. x = 0.5 Simplifying x = 0.5
| 5(3+4x)-2=33 | | 8x-3=11+6x | | 3x+7(4x-12)=133 | | 3x+3x=144 | | 2v^2+3=-7v | | y^2+18xy+81x^2= | | 1/2x-1/3(x-8)=3x | | 3x+5(x-7)=5 | | 5x+(-13y)+(-x)+11y= | | 2x+5(x+2)=80 | | 8=3(3-x) | | r-17=-33 | | 2x+2x+2x=69 | | x+50000=600000000 | | 1/5x+1/2=-2 | | (x-2)(x+2)12-(x^2-4)(x+2)3=(x^2-4)(x-2)9 | | 81a^2-25= | | 6x+2(5x+5)=122 | | 3x+3x=132 | | -40x^2-47x-12= | | x+5/2=10 | | x/2+24=78 | | 10(t-3)+5t=5(3t+4)-10 | | 3m-5=m+3 | | 5x1/2x1x2/7 | | 2x+2x=84 | | w+20+s=288 | | 10(t-3)+4t=7(2t+3)-11 | | 24x^5-4x^4= | | (x-2)2x+4-(2)3x=2(x-2)x | | -17=4+3w | | 2(4+x)=48 |